Liver Function Testing Is Not Useful in the Diagnosis of Sarcoidosis in Patients Presenting with Uveitis. (4th May 2017) - Jones, Nicholas P.
ABSTRACT: Purpose : To elucidate the usefulness of abnormal liver function tests in the diagnosis of sarcoidosis in patients presenting with ocular inflammation. Methods : Retrospective comparison of sample populations of 100 patients each with sarcoidosis-associated uveitis (SAU) and non-sarcoid uveitis controls. Results : Number of abnormal results between SAU and control groups were: (1) raised alkaline phosphatase 6:2; (2) raised alanine aminotransferase 21:19; (3) raised total protein 14:5; (4) hypoalbuminemia 0:7; (5) raised bilirubin 1:2. The only parameters reaching statistical significance were in (3), using any elevated result; and (4), the greater risk being in controls. Conclusions : There is no evidence that abnormal liver function tests are an indicator of sarcoidosis in new patients presenting with uveitis.